1989
DOI: 10.1289/ehp.8982323
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional receptor model for dioxin and related compound toxic action: possible thyroid hormone-responsive effector-linked site.

Abstract: Molecular/theoretical modeling studies have revealed that thyroid hormones and toxic chlorinated aromatic hydrocarbons of environmental significance (for which dioxin or TCDD is the prototype) have similar structural properties that could be important in molecular recognition in biochemical systems. These molecular properties include a somewhat rigid, sterically accessible and polarizable aromatic ring and size-limited, hydrophobic lateral substituents, usually contained in opposite adjoining rings of a diphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 77 publications
1
36
0
Order By: Relevance
“…The observation of structure similarities between TCDD and thyroid hormones prompted structureactivity relationship (Cheek et al 1999;McKinney and Waller 1998) and in-vitro competitive binding studies (Cheek et al 1999;McKinney 1989) that confirmed that TCDD properties resemble those of thyroid hormones triiodothyroxine (T 3 ) and thyroxine (T 4 ) (Porterfield 2000). However, affinity of dioxin-like compounds is low for thyroid receptor and elevated for serum transport proteins (Cheek et al 1999).…”
Section: Structure Similarities Between Tcdd and Thyroid Hormonesmentioning
confidence: 93%
See 2 more Smart Citations
“…The observation of structure similarities between TCDD and thyroid hormones prompted structureactivity relationship (Cheek et al 1999;McKinney and Waller 1998) and in-vitro competitive binding studies (Cheek et al 1999;McKinney 1989) that confirmed that TCDD properties resemble those of thyroid hormones triiodothyroxine (T 3 ) and thyroxine (T 4 ) (Porterfield 2000). However, affinity of dioxin-like compounds is low for thyroid receptor and elevated for serum transport proteins (Cheek et al 1999).…”
Section: Structure Similarities Between Tcdd and Thyroid Hormonesmentioning
confidence: 93%
“…A variety of chemicals have been identified that may interfere with synthesis, secretion, transport, metabolism, or receptorial actions of endogenous hormones. Analysis of TCDD chemical structure reveals that TCDD bears a structural resemblance to the natural thyroid hormones (Baccarelli et al 2000;McKinney 1989). Proteins that bind thyroid hormones in vivo may also bind to TCDD and other structure-related compounds.…”
Section: Mechanisms Of Dioxin Toxic Effects On Thyroid Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prenatal exposure to PCBs/dioxins in laboratory animals induces a decrease in plasma T4 levels without significantly altering the growth [57], and T3 levels remain within the normal range [58], indicating that the toxicity of these chemicals does not manifest by altering blood TH levels. On the other hand, because the molecular structures of PCBs/dioxins are similar to those of TH, these chemicals are considered to act via TH receptors (TRs) [59]. Furthermore, these compounds can be transferred across the blood-brain barrier and accumulate in the brain [60].…”
Section: Polychlorinated Biphenols (Pcbs)mentioning
confidence: 99%
“…TCDD does not bind to the different receptor proteins involved in this system. However, interaction with a hypothetical thyroxine receptor has been proposed as a mechanism for the thyroxine-like effects produced by TCDD in some systems (McKinney et al 1985(McKinney et al , 1989Jones et al 1987). Osborne et al (1987) found that neither TCDD nor tetrachlorodibenzofuran altered thyroid hormone binding to nuclear thyroid hormone receptors.…”
Section: Hypotheses On the Mode Of Actionmentioning
confidence: 99%